2022
DOI: 10.3390/ijms23105354
|View full text |Cite
|
Sign up to set email alerts
|

Short-Chain Fatty Acids in Chronic Kidney Disease: Focus on Inflammation and Oxidative Stress Regulation

Abstract: Chronic Kidney Disease (CKD) is a debilitating disease associated with several secondary complications that increase comorbidity and mortality. In patients with CKD, there is a significant qualitative and quantitative alteration in the gut microbiota, which, consequently, also leads to reduced production of beneficial bacterial metabolites, such as short-chain fatty acids. Evidence supports the beneficial effects of short-chain fatty acids in modulating inflammation and oxidative stress, which are implicated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 173 publications
1
46
0
Order By: Relevance
“…Previous reviews published about the effects of SCFAs on energy metabolism have either focused solely on diet [ 32 ] or on specific diseases related to obesity and metabolic syndrome [ 33 , 34 , 35 ]. The aim of this review is to provide an overview and analysis of the variations of SCFAs in feces and blood in obesity and metabolic syndrome and to identify novel ways to approach the monitoring of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews published about the effects of SCFAs on energy metabolism have either focused solely on diet [ 32 ] or on specific diseases related to obesity and metabolic syndrome [ 33 , 34 , 35 ]. The aim of this review is to provide an overview and analysis of the variations of SCFAs in feces and blood in obesity and metabolic syndrome and to identify novel ways to approach the monitoring of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Depletion of bacteria responsible for the production of beneficial short-chain fatty acids (SCFAs), such as acetate, propionate, and butyrate, in the setting of a disrupted gut microbiome may lead to deleterious effects in the liver and kidney. These SCFAs could promote anti-inflammatory and anti-oxidative actions by limiting neutrophil recruitment, macrophage secretion of pro-inflammatory mediators, and histone deacetylase-induced NF-κB activation while promoting anti-inflammatory interleukin-10 formation by T regulatory cells[ 55 ]. Increased availability of SCFA-producing bacteria or SCFA treatment in clinical studies of patients on hemodialysis patients has resulted in lowering inflammatory markers and ameliorating renal function[ 56 , 57 ].…”
Section: Pathophysiologic Pathways Linking Mafld With Ckdmentioning
confidence: 99%
“…An animal study, using an adenine-induced mouse model of chronic kidney disease (CKD), showed that propionic acids, via FFA2 and FFA3 receptors, inhibit the expression of pro-inflammatory factors, and significantly reduce serum creatinine (Cr) and urea nitrogen levels [132]. Another study showed that the key mechanism of SCFAs against acute kidney injury (AKI) is local and systemic reduction of inflammatory cytokine and chemokine production through inhibition of LPS-TLR4-induced NF-κB and MAPK inflammatory signaling pathways, which may be related to GPCRs activation and autophagy regulation [133] [134] [135]. In addition, renal anemia is a serious complication of chronic kidney disease (CKD) and current erythropoietic and iron supplementation treatments have limitations.…”
Section: Scfas and Urinary Systemmentioning
confidence: 99%